2022
DOI: 10.1111/jocd.15206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial and wound‐healing activities of alcoholic extract of Boswellia carterii, in vitro and in vivo study

Abstract: Wounds are defined as the cellular and anatomical destruction of tissues that can be caused by chemical, physical, microbiological, thermal, or immunological damage, leading to skin rupture. 1 Wound healing is one of the most complex biological processes, with four overlapping phases: hemostasis, inflammation, proliferative, and maturation. These phases lead to the regeneration of new tissue. In burn injuries, blood coagulation occurs due to damaged capillaries, followed by inflammation. 2,3 The global cost of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Thujene has been reported to be one of the main components of many essential oils. It has shown strong antibacterial and wound‐healing activities in skin care products (Hasson et al., 2022). Yang et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thujene has been reported to be one of the main components of many essential oils. It has shown strong antibacterial and wound‐healing activities in skin care products (Hasson et al., 2022). Yang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Thujene has been reported to be one of the main components of many essential oils. It has shown strong antibacterial and wound-healing activities in skin care products (Hasson et al, 2022). Yang et al (2015) demonstrated that terpinen-4-ol could be released from a solid terpinen-4-ol/β-cyclodextrin, resulting in enhanced antibacterial activity against S. aureus and E. coli, with concentrations ranging from 1.25 to 5 mg/mL.…”
Section: Compoundsmentioning
confidence: 99%
“…Ointment was initially selected as the formulation since it has the ability to remain on surfaces longer than liquid formulations, and is also easy to rub 12 . To prepare an ointment with a uniform consistency and smooth texture of ithmid kohl/ZnONPs, 2.5 g of ithmid kohl and 2.5 g of ZnONPs were mixed with commercially available Vaseline (up to 100 g).…”
Section: Methodsmentioning
confidence: 99%
“…The ointment was transferred to a clean container and stored in the refrigerator (+ 4 °C) until use. The above-mentioned concentrations were randomly selected to carry out a preliminary study 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation